KRITIK METODOLOGI PENAFSIRAN BUCAILLISME ATAS AYAT-AYAT SAINS - Permono, Ajar (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
Discourse on scientific theology is quite often lead to debate among scholars and scientists today. The central point of the debate is on the relationship between the Qur’an dan science, namely the Total Agreement, Partial Agreement and the Refuse Group. Bucaillism as representation the Total Agreement group has the view that the Quran besides functioning as a moral-ethical guideline and guidance is also the source of all the phenomena of science. This article to photograph what and how bucaillism, find the cause and do methodological criticisms on it. This research concludes that the tendency towards the progress of science becomes an important point in the progress of the civilization of Muslims. With the harmonization of science and religion, it can increase creativity and innovation in doing business in making discoveries. Qur’an which contains many creeds and moral-ethical and verses of science can be a guide for scientists in developing science and technology so that the benefit of humans and the environment is always maintained. Nevertheless, the argumentative basis in scientific research is not only based on the literal meaning of the text but leads to the moral-ethical content. Keyword: Bucaillism, Quran, Phenomena of Science